PENGARUH SIFAT MACHIAVELLIAN, LINGKUNGAN ETIKA, KOMITMEN ORGANISASI, DAN TINGKAT KESERIUSAN KECURANGAN TERHADAP NIAT MELAKUKAN WHISTLEBLOWING (Studi Empiris pada BPKAD di Kota Padang) - Sartika, Dewi; Mulyani, Fitrah (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
This study aims to determine the influence of machiavellian nature, ethical environment, organizational commitment and the level of seriousness of cheating on the intention to do whistleblowing. This research is a causal study with a quantitative approach that explains empirical phenomena. This study uses a population of 83 respondents with data that can be processed as many as 60 respondents who are all employees who work at BPKAD, who are in the Padang area. This study uses primary data from questionnaires and interviews, and secondary data from notes or documentation, and government publications. Data were analyzed using multiple regression analysis which is processed through SPSS 21. The results of the study concluded that the machiavellian nature does not affect the intention to do whistleblowing, this is because if someone who has a tendency to high machiavellian traits he will only act more emotionally, because to do whistleblowing is not easy in reporting an act of violation or fraud. That the ethical environment influences the intention to do whistleblowing, this is because if an organization or government or private agency has a good and strong ethical environment, which leads to positive things, then employees who are in the organization will want to take whistleblowing actions, because this in accordance with applicable norms. That organizational commitment does not affect the intention to do whistleblowing, this is due to an organization that has a low organizational commitment among its employees, which results in lack of faith and loyalty. That the level of seriousness of fraud does not affect the intention to conduct whistleblowing. It can be concluded that when tested together, the variable machiavellian nature (X1), ethical environment (X2), organizational commitment (X3), and the level of seriousness of fraud (X4) affect the intention to do whitlebowing (Y). Keywords: Machiavellian Nature, Ethical Environment, Organizational Commitment, Seriousness Level of Cheating, Whistleblowing